Centipede inside ear: utility of video otoscopy - Choorisaz, Umer Sharief (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Patients with ear related symptoms constitute a considerable group visiting primary health centres. Video otoscope is an upgraded version of traditional otoscope equipped with features that make it suitable for use among primary care physicians in diagnosing the diseases of ear and in removal of foreign bodies from ear. A 5-year-old child presented with sudden onset left ear pain and itching that woke her up from sleep. Examination with a video otoscope revealed a non-motile insect-like foreign body in the external auditory meatus. Upon proper removal under the guidance of video otoscopy, it was found to be a centipede mingled with cerumen. Contra lateral ear was also cleared of impacted cerumen. Patient’s ear ache and sense of ear blockage resolved and patient continued to be symptom free on follow-up. Video otoscopy is a useful technique and its introduction in primary care settings may lead to a better management of patients with ear related complaints.